Proceedings of Social Sciences, Humanities and Economics Conference (SoSHEC 2017) 2018
DOI: 10.2991/soshec-17.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Competence of English Subject at Junior Middle School Having Low and High Order Thinking Skills

Abstract: The purpose of this paper is to find out which contents of core and basic competence of English subject have low-order thinking skills (LOTS) and higher-order thinking skills (HOTS) at Junior Middle School. It discusses that learning taxonomies having six levels: remembering, understanding, implementing, analysing, assessing, and creating. The levels of taxonomies are classified by two kinds of groups. The first three groups is low-order thinking skills (LOTS), and the second three groups is higher-order think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Those examined frequently in numerous textbooks [2] and English language skills: writing, speaking, reading comprehension and others. Hence, in countless research, the studies revealed that critical thinking is evidently related to The Bloom's taxonomy specifically the skills of analyzing, evaluating, and creating [2];; [8]; [9]; [10]. Moreover, it is recognized that Bloom's taxonomy is the pioneer to initiating critical thinking categories skills of analyzing, evaluating and creating.…”
Section: B the Revised Bloom's Taxonomy And Critical Thinkingmentioning
confidence: 99%
“…Those examined frequently in numerous textbooks [2] and English language skills: writing, speaking, reading comprehension and others. Hence, in countless research, the studies revealed that critical thinking is evidently related to The Bloom's taxonomy specifically the skills of analyzing, evaluating, and creating [2];; [8]; [9]; [10]. Moreover, it is recognized that Bloom's taxonomy is the pioneer to initiating critical thinking categories skills of analyzing, evaluating and creating.…”
Section: B the Revised Bloom's Taxonomy And Critical Thinkingmentioning
confidence: 99%
“…These two cognitive competency levels are chosen for the close relation between evaluating and creating level and critical thinking (Setyowati, 2019). (Aghaei, 2018), (Thomas, 2017), (Zuhri, 2018) and (Ebadi, 2016) found that in particular, the skills of analyzing, evaluating and creating are the indicators of critical thinking. Thus, the usage of taxonomy Bloom is shown in the increment of students' critical thinking.…”
Section: Introductionmentioning
confidence: 99%